Pregorexia: a reflection on the influence of social networks on self-image and on the development of eating disorders during pregnancy (Research, Society and Development, 2022)
Pregorexia occurs in women during the period of pregnancy, it is a type of behavior. Its etiology is similar to that of anorexia nervosa, since pregnant women with pregorexia restrict their daily calorie intake, adhering to extreme styles in relation to self-image. This study has the General Objective: To reflect on the aspects that define Pregorexia and its influence on self-image through social media. As specific objectives: To present what Pregorexia is; highlight the development of eating disorders during pregnancy; to verify about the role of the nutritionist in the management of people with eating disorders. The methodology of the bibliographic research was a systematic review study, with a qualitative approach. Data for analysis were collected from scientific articles, books and journals already published, accessed from sources on Google Scholar and Scielo. As inclusion criteria for this study, bibliographic materials were selected according to the content relevance for insertion in the study, in Portuguese and foreign languages, with free access, emphasizing the terms related to the descriptors: Pregnancy; Social media; eating disorders; Pregorexia. Organized according to the VHL - Virtual Health Library, DeCS - Descriptors in Health Sciences. As for the exclusion of articles, it took place through those that were unrelated to the proposed theme, and those with paid access. Studies such as this one are important to provide a better understanding of the phenomena of social networks and the influence on eating behavior and the development of eating disorders in pregnancy, such as Pregorexia.